Data from Archaeology for the People? Greek Archaeology and its Public: An Analysis of the Socio-Political and Economic Role of Archaeology in Greece - Anastasia Sakellariadi (Journal of Open Archaeology Data, 2015)
The interview transcripts and survey data in this dataset originate from an investigation of the role of archaeology in local communities in Greece today. The communities of Krenides (Kavala), Dispilio (Kastoria) and Delphi (Phokida) were used as case studies. Members of these communities, local archaeologists and archaeologists of the central services of the Ministry of Culture were interviewed while the local populations were surveyed using structured questionnaires. The data is stored in textual and tabular formats and it is likely to be of use to anyone who is interested in public archaeology, heritage management or socio-anthropological and sociological research regarding perceptions about the past, archaeology and heritage.